2005
DOI: 10.1111/j.1365-277x.2005.00631.x
|View full text |Cite
|
Sign up to set email alerts
|

Energy intakes of children with Crohn's disease treated with enteral nutrition as primary therapy

Abstract: Estimated average requirement underestimates energy intakes in most children with newly diagnosed Crohn's disease. During EN, an energy intake in the range of 100-149% (median 117.5%) EAR for energy for age may be required. Energy balance studies in children with active disease are required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
1
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 11 publications
2
24
1
1
Order By: Relevance
“…14 EAR underestimated TEE in larger children by up to 1477 kcal/d and overestimated TEE in smaller children by as much as 663 kcal/d, thus illustrating the inherent problems of applying population average requirements in clinical practice. The measured values for REE per kg fat free mass are similar in this study to those measured in the studies by Azcue et al 38 and Varille et al 39 Gavin et al 15 performed an intake study on children with active CD, fed exclusively EN. Forty children with varying disease sites were fed EN to appetite for 8 weeks.…”
Section: Energy Requirementssupporting
confidence: 71%
See 1 more Smart Citation
“…14 EAR underestimated TEE in larger children by up to 1477 kcal/d and overestimated TEE in smaller children by as much as 663 kcal/d, thus illustrating the inherent problems of applying population average requirements in clinical practice. The measured values for REE per kg fat free mass are similar in this study to those measured in the studies by Azcue et al 38 and Varille et al 39 Gavin et al 15 performed an intake study on children with active CD, fed exclusively EN. Forty children with varying disease sites were fed EN to appetite for 8 weeks.…”
Section: Energy Requirementssupporting
confidence: 71%
“…It is worth noting, however, that 82% of children with Crohn's consumed in excess of their estimated average requirements (EAR) 14 when fed exclusively enteral nutrition (EN) to satisfy their hunger, as primary therapy for active disease. 15 Pragmatically, a decreased appetite occurs for many reasons. Patients feel too unwell to eat, have considerable malaise, and often have persistent epigastric and abdominal discomfort.…”
mentioning
confidence: 99%
“…In addition to inducing remission, EEN had the benefit of improving anthropometric parameters after the initial course as well as at follow-up. 13,25,26 The amount of weight gain during an 8 week course of EEN varies [26][27][28] which could be explained in part by different participant characteristics and study designs. Different types of formula have been used in various studies but according to current literature there are no compositional differences between them which should affect growth parameters.…”
Section: Resultsmentioning
confidence: 99%
“…Some studies demonstrated increased energy requirements in active disease, 14 -16 and it has been suggested that although increased resting energy expenditure (REE) is present with active disease, there is no change in total energy expenditure due to decreased physical activity. 16 Azcue et al 17 showed that despite being malnourished, children with CD fail to adapt their REE per unit of lean body mass, thus contributing to their malnutrition. In addition, measured REE for parenterally fed CD patients was shown to be similar to the predicted REE, indicating that REE for the parenterally fed pediatric patients with CD can be accurately predicted using the FAO/WHO/UNU equations.…”
Section: Disease-related Factors Nutritionmentioning
confidence: 98%